Patterns and Causality Assessment of Adverse Drug Reactions in Inpatients of a Tertiary Care Hospital, Nepal - Mudvari, Anish; Yadav, Dipendra; Ghimire, Rakesh; Prasad, Pravin (Journal of Institute of Medicine Nepal, 2020)
Introduction Adverse drug reaction (ADR) is a leading cause of morbidity and mortality around the world. Causality assessment is done to establish relation of drug exposure with undesired clinical events. This study conducted in tertiary care hospital was undertaken to evaluate the patterns of ADR and causality assessment using Naranjo causality algorithm.MethodsData on suspected ADR cases were collected retrospectively from Medicine and Dermatology wards of Tribhuvan University Teaching Hospital, Kathmandu from April 2018 to April 2019. Naranjo causality assessment was performed. Statistical analysis was done using SPSS version 18.ResultsOf 34 suspected ADR, occurrence of ADR was more in females (18) as compared to males (16). Skin and integumentary system was the most common organ affected (35.29%). Pyrazinamide induced hepatitis was found to be the most common suspected ADR. Causality assessment was performed and ADRs were categorized as possible 17 (50%), probable 16 (47.06%) and definite 1 (2.94%).ConclusionThe patients are commonly admitted at the hospital due to suspected ADRs. Pyrazinamide induced hepatitis was the most common suspected ADR.